The Practice of Mindfulness in the Classroom its impact on students’ Academic performance: A Review Based on available literature - Prabhu (MultiTech Publisher, 2023)
The present system of teaching learning is not effective enough to make student focus and have maximum attention in the class room during teaching learning process which has a risk of loosing the significance of structured or formal education. Mindfulness or meditation in the classroom has significant effects and benefits for students. This paper aims to identify the benefits of mindfulness and its practice in class room among students in their education and academic performance.